Al-Haq : A Global History of the First Palestinian Human Rights Organization. - Welchman, Lynn. (New Directions in Palestinian Studies, 2021)
A free open access ebook is available upon publication. Learn more atwww.luminosoa.org. The leadership and legacy of al-Haq, from its origins in Palestine to its international impact Established in Ramallah in 1979, al-Haq was the first Palestinian human rights organization and one of the first such organizations in the Arab world. This inside history explores how al-Haq initiated methodologies in law and practice that were ahead of its time and that proved foundational for many strands of today's human rights work in Palestine and elsewhere. Lynn Welchman looks at both al-Haq's history and legacy to explore such questions as: Why would one set up a human rights organization under military occupation? How would one go about promoting the rule of law in a Palestinian society deleteriously served by the law and with every reason to distrust those charged with implementing its protections? How would one work to educate overseas allies and activate international law in defense of Palestinian rights? This revelatory story speaks to the practice of local human rights organizations and their impact on international groups.